Effects of stress and mental toughness on burnout and depressive symptoms: A prospective study with young elite athletes. Issue 12 (December 2018) - Gerber, Markus; Best, Simon; Meerstetter, Fabienne; Walter, Marco; Ludyga, Sebastian; Brand, Serge; Bianchi, Renzo; Madigan, Daniel J.; Isoard-Gautheur, Sandrine; Gustafsson, Henrik
Abstract: Objectives: To examine in a sample of young elite athletes (a) the presence of clinically relevant symptoms of burnout and depression, and (b) a possible interaction of perceived stress and mental toughness in the prediction of burnout and depressive symptoms. Design: 6-month prospective study. Methods: A representative sample of 257 young elite athletes ( M  = 16.82 years, SD  = 1.44, 36% females) was recruited in North–Western Switzerland. 197 athletes were followed-up across a 6-month period. Burnout was assessed with the Shirom-Melamed Burnout Measure (SMBM), and depression with the 9-item depression module of the Patient Health Questionnaire (PHQ). Values of ≥4.40 (SMBM) and >14 (PHQ-9) were considered indicative of clinically relevant burnout or depression. Stress perceptions were assessed with the Perceived Stress Scale (PSS), and mental toughness with the Mental Toughness Questionnaire (MTQ). Hierarchical regression analyses were used to test stress-buffering effects. Results: The percentage of athletes with clinically relevant levels of burnout and depressive symptoms was 12% and 9%, respectively. Both cross-sectional and prospective analyses showed that compared to participants with low mental toughness, those with higher mental toughness scores reported significantly fewer mental health issues, when exposed to high stress. By contrast, when stress levels were low, mental toughness was unrelated to psychological health complaints. Conclusions: About every tenth young elite athlete reported burnout or depressive symptoms of potential clinical relevance. While high perceived stress was associated with increased psychological health complaints, mental toughness was able to off-set some of the negative consequences resulting from high stress exposure.